THE INFLUENCE OF PRODUCT QUALITY AND PROMOTION TO CUSTOMER’S PURCHASE DECISION AT RAGEY 21 POLITEKNIK - Natalia V. P. Wurarah; Paulus Kindangen; Merinda H. C. Pandowo (Universitas Sam Ratulangi, 2022)
Abstract: Nowadays, there are many business competitors that causing many choices for the customers to make a purchase. Therefore, the company must carry out the marketing strategy properly in order to attract customer’s purchase decision. Good product quality and attractive promotions are important factors in customer purchase decision process so that repeat purchases can occur. The aims of this research are to analyze the influence of product quality and promotion to customer purchase decision in Ragey 21 Politeknik. This research uses questionnaires data collection techniques with the respondent data of 100 people. This study uses Multiple Linier Regression with the help of SPSS 25. The result of this study showed that product quality and promotion has a positive influence on customer purchase decision partially. Simultenously, product quality and promotion has a positive influence on customer purchase decision. It is important for Ragey 21 to keep building and maintaining the quality of the product. The promotions have been done well, it needs to be improved in the delivery of information to the customer, so that the customer can easily recognize and comprehend the information provided. Keywords: product quality, promotion, customer purchase decision